Autonomous mechanism of simultaneous synthesis in the processes of reproductive problems solving - Polikarpov, Vladimir A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
An experimental psychological study of thinking is carried out through an analysis of the process of solving the problems of the thinking of the subjects. All experimental mental tasks can be divided into reproductive and creative. Reproductive concerns such problems, a method for solving which is available in the subject’s experience. The solution of reproductive problems is realized through a specific mechanism of thinking – an autonomous mechanism of simultaneous synthesis. This mechanism automatically reacts to the way the organization of the task material in its problematic part and actualizes the appropriate way of organization of the solution, previously solved tasks, similar in the manner of organizing the problem part with the problem.